Dose proportionality and pharmacokinetics of carvedilol sustained-release formulation: a single dose-ascending 10-sequence incomplete block study - Kim YH; Choi HY; Noh YH; Lee SH; Lim HS; Kim C; Bae KS (Drug Design, Development and Therapy, 2015)
Yo Han Kim,1 Hee Youn Choi,1 Yook-Hwan Noh,1 Shi Hyang Lee,1 Hyeong-Seok Lim,1 Chin Kim,2 Kyun-Seop Bae11Department of Clinical Pharmacology and Therapeutics, College of Medicine, University of Ulsan, Asan Medical Center, 2Chong Kun Dang Clinical Research and Clinical Epidemiology and Medical Information, CKD Pharmaceuticals, Seoul, Republic of KoreaBackground: Carvedilol is a third-generation β-blocker indicated for congestive heart failure and high blood pressure. The aim of this study was to investigate the dose proportionality of the carvedilol sustained-release (SR) formulation in healthy male subjects.Methods: An open-label, single dose-ascending, 10-sequence, 3-period balanced incomplete block study was performed using healthy male subjects. In varying sequences, each subject received three of five carvedilol SR formulations (8, 16, 32, 64, or 128 mg once). The treatment periods were separated by a washout period of 7 days. Serial blood samples were collected up to 48 h after dosing. The plasma concentrations of carvedilol were determined by using validated liquid chromatography–tandem mass spectrometry. Pharmacokinetic parameters including the area under the plasma concentration–time curve (AUC) from time 0 to the last measurable time (AUClast), AUC extrapolated to infinity (AUCinf), and the measured peak plasma concentration (Cmax) were obtained by noncompartmental analysis. Dose proportionality was evaluated if the ln–ln plots of AUClast, AUCinf, and Cmax versus dose were linear and the 90% confidence intervals (CIs) of the slopes were within 0.9195 and 1.0805. Tolerability was assessed by vital signs, electrocardiogram, clinical laboratory tests, and monitoring of adverse events (AEs) throughout the study.Results: A total of 31 subjects were enrolled, and 30 completed the study. The assessment of dose proportionality meets the statistical criteria; the point estimates of slope were 1.0104 (90% CI: 0.9849–1.0359) for AUClast, 1.0003 (90% CI: 0.9748–1.0258) for AUCinf, and 0.9901 (90% CI: 0.9524–1.0277) for Cmax, respectively. All AEs were mild, and none of the subjects dropped out due to AEs.Conclusion: In this study, exposure to carvedilol was proportional over the therapeutic dose range of 8–128 mg. The carvedilol SR formulation was well tolerated. Keywords: dose linearity, carvedilol, sustained release, healthy subjects